Recombinant Calponin of human filariid Brugia malayi: Secondary structure and immunoprophylactic potential. Issue 38 (12th September 2017) - Verma, Shiv K.; Arora, Ashish; Murthy, P. Kalpana
Highlights: Calponin-like protein of Brugia malayi (ClpBm) was cloned & r-ClpBm was prepared. r-ClpBm was mainly in α-helix folding & is present in all life-stages of the parasite. r-ClpBm immunization partially protected host from B. malayi via Th1, Th2, NO and mast cells. r-ClpBm may further be studied as a component of potential filarial cocktail vaccine candidate. Abstract: In the search for potential vaccine candidates for the control of human lymphatic filariasis, we recently identified calponin-like protein, that regulates actin/myosin interactions, in a proinflammatory fraction F8 (45.24–48.64 kDa) of Brugia malayi adult worms. In the present study, the gene was cloned, expressed, and the recombinant Calponin of B. malayi (r-ClpBm) was prepared and characterized. r-ClpBm bears homology with OV9M of Onchocerca volvulus, a non-lymphatic filariid that causes loss of vision and cutaneous pathology . r-ClpBm was found to be a ∼45 kDa protein that folds into a predominantly α-helix conformation. The protective efficacy of r-ClpBm against B. malayi infection in Mastomys coucha was investigated by assessing the course of microfilaraemia and adult worm burden in the host immunized with r-ClpBm and subsequently infected with infective third stage larvae (L3 ). Expression of the Calponin was detected in all life stages (microfilariae, L3, L4, L5 and adults) of the parasite and immunization with r-ClpBm partially protected M. coucha against establishment of infection as inferred by ∼42% inhibition in parasite burden. Upregulated cellular proliferation, TNF-α, IFN-γ, IL-1β, IL-4, nitric oxide (NO) release, expression of iNOS, and specific IgG, IgG1 and IgG2b in immunized animals correlated with parasitological findings. r-ClpBm immunization caused degranulation in majority of mast cells indicating possible involvement of mast cell products in reducing the parasite survival. It appears that complex mechanisms including Th1, Th2, NO and mast cells are involved in the clearance of infection. To the best of our knowledge this is the first report on cloning, expression of the gene and purification of r-ClpBm, determination of its secondary structure and its ability to partially prevent establishment of B. malayi infection. Thus, r-ClpBm may further be studied and developed in combination with other protective molecules of B. malayi as a component of potential filarial cocktail vaccine candidate.